REGENERATIVE PERIODONTAL TREATMENT AS MANAGEMENT OF CHRONIC PERIODONTITIS: A CASE REPORT - Ainun Isnaeni Ilham; Daniel Tetan El; Sri Oktawati (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Chronic periodontitis is a chronic inflammatory disease induced by microbes beginning with inflammation of the gingiva and progressing to progressive damage to the tooth supporting structures. Various approaches have been made to treat chronic periodontitis, one of which is regenerative periodontal treatment using bone grafts and platelet-rich fibrin (PRF). History and Clinical Findings: A 32-year-old man came to the Periodontology Department of the Dental and Oral Education Hospital with chief complaints mobility of upper and lower teeth. Clinical examination showed that patient did not have a history of systemic diseases and the patient did not smoke. Intraoral examination showed that the maxillary front teeth grade 1 mobility and the average pocket depth in the maxillary and mandibular anterior teeth was 5 mm. Case Management: Case management includes initial therapy followed by surgical treatment which includes open flap, placement of bone graft and PRF, followed by frenectomy, then suturing and application of a periodontal pack. At 1 month after treatment, the surgical flap phase was continued for the mandibular anterior teeth using a combination of bone graft and membrane placement. Discussion: Bone graft and PRF are used to regenerate furcation defects and their ability to regenerate hard and soft tissue is due to the release of various growth factors. Conclusion: Regenerative surgical treatment in chronic periodontitis patients provides effective results in alveolar bone regeneration and decrease pocket depth.